2015
DOI: 10.1186/s40851-014-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic adaptation and the evolution of smell and taste in whales

Abstract: IntroductionWhile olfaction is one of the most important senses in most terrestrial mammals, it is absent in modern toothed whales (Odontoceti, Cetacea). Furthermore, behavioral evidence suggests that gustation is very limited. In contrast, their aquatic sistergroup, baleen whales (Mysticeti) retain small but functional olfactory organs, and nothing is known about their gustation. It is difficult to investigate mysticete chemosensory abilities because experiments in a controlled setting are impossible.ResultsH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 56 publications
(82 reference statements)
5
117
0
1
Order By: Relevance
“…Taste receptor genes are reported to be mostly pseudogenized in Odontoceti: in bottlenose dolphins, sweet, umami, bitter and sour taste receptor genes are non-functional, whereas salty taste receptor genes are intact and potentially have functional roles in gustation (Jiang et al, 2013;Feng et al, 2014;Kishida et al, 2015b). Recent molecular findings suggest that this reduction of gustatory abilities in cetaceans occurred between the Artiodactyla-Cetacea and the Odontoceti-Mysticeti evolutionary divisions (Kishida et al, 2015b).…”
Section: Physiological Data On Gustationmentioning
confidence: 99%
See 2 more Smart Citations
“…Taste receptor genes are reported to be mostly pseudogenized in Odontoceti: in bottlenose dolphins, sweet, umami, bitter and sour taste receptor genes are non-functional, whereas salty taste receptor genes are intact and potentially have functional roles in gustation (Jiang et al, 2013;Feng et al, 2014;Kishida et al, 2015b). Recent molecular findings suggest that this reduction of gustatory abilities in cetaceans occurred between the Artiodactyla-Cetacea and the Odontoceti-Mysticeti evolutionary divisions (Kishida et al, 2015b).…”
Section: Physiological Data On Gustationmentioning
confidence: 99%
“…However, OR genes are reported to be functionally reduced by pseudogenization in Odontoceti (Kishida et al, 2007). Bottlenose dolphins possess only two class I and ten class II OR genes that are intact, as well as a single vomeronasal receptor type 1 gene (Kishida et al, 2015b).…”
Section: Anatomical Data On Olfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of paleontological evidence in evolutionary arguments is clear, as is seen in assessments of animal bodies from the perspectives of comparative morphology, embryology, genomic, and developmental biology. Kishida et al (2015), for example, have demonstrated that baleen whales lost the dorsal domain of the olfactory bulb, known to induce innate avoidance behavior against odors of predators and spoiled foods, before the toothed and baleen whale split based on not only whole genome sequences but also fossil data, indicating that profound changes in the chemosensory capabilities had occurred in the cetacean lineage during the period when ancestral whales migrated from land to water. Shone et al (2016) evaluated fossil agnathan morphological traits to speculate about an evolutionary sequence in vertebrate gill number.…”
Section: To Enhance Evolutionary Studiesmentioning
confidence: 99%
“…Hirasawa and Kuratani, 2015;Hojo et al, 2015;Tada and Kuratani, 2015;Hayashi et al, 2015;Nakano, 2015;Onai et al, 2015a, b;Oisi et al, 2015;Shigeno et al, 2015;Kaji et al, 2016;Takeuchi et al, 2016;Suzuki et al, 2016;Hirasawa et al, 2016), a clear trend dating to the launch year, as we reported in a previous review (Fukatsu and Kuratani, 2014). Nonetheless, ZL is open to all areas of basic zoology, and many of the top cited and most frequently accessed papers have been from fields other than evo-devo (Holland, 2015;Kishida et al, 2015;Inoue et al, 2015;Mizunami et al, 2015;Hosokawa et al, 2015;Moriyama and Numata, 2015). Thanks to its affiliation with the Zoological Society of Japan, ZL initially received many contributions from Japanese zoologists, but as international recognition for the journal has grown, papers contributed by authors from other countries have continued to increase.…”
Section: Introductionmentioning
confidence: 99%